Pelatihan Pembuatan Konten Media Sosial: Cara Memulai Konten Media Sosial di Tahun 2024 di SMK YBPK Pare - Ichwan Setiarso; Khamadi Khamadi; Widyatmoko Widyatmoko; Micail Dewasyah Putra; Bernadheta Novia (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2026)
Abstract. The rapid growth of social media has significantly changed communication patterns, self-expression, and employment opportunities, especially among younger generations. However, among vocational high school students, social media use is still largely focused on entertainment and has not been optimally utilized for skill development, personal branding, or economically productive activities. Addressing this issue, a community service program was conducted to enhance the knowledge, understanding, and practical skills of students at SMK YBPK Pare in creating creative, structured, and relevant social media content in line with the demands of the digital era in 2024. The program was implemented through the delivery of conceptual materials on social media fundamentals, content planning strategies, and effective content creation techniques. These materials were strengthened through interactive discussions and hands-on practice using smartphones and accessible editing applications. The participants included 40 students from grades X, XI, and XII, representing Generation Z with high social media usage intensity. The results showed improved student understanding of the purpose of social media, basic digital content concepts, and communicative content creation techniques. Students were able to produce simple promotional content to support school branding. In addition to technical skills, the program increased awareness of social media as a tool for self-development, digital literacy, and future employment or entrepreneurial opportunities, thereby contributing positively to students’ digital competencies and work readiness.